Product design and manufacturing : selected, peer reviewed papers from 2011 International Conference on Materials and Products Manufacturing Technology (ICMPMT 2011), October 28-30, 2011, Chengdu, China - Zhang, Xiaodong (Advanced materials research, 2011)
The papers in this book were the object of strict peer-review, and cover the latest advances in, and applications of, advanced design technology, CAD/CAM/CAE, mechanical dynamics, friction and wear and advanced manufacturing technologies. Review from Book News Inc.: The areas covered are advanced design technology; computer-aided design, manufacturing, and engineering; mechanical dynamics and its applications; and friction and wear. The some 150 papers discuss such matters as applying the single-point incremental forming technology of sheet metal in bus prototyping, creep behavior and mechanic.